Odczytując palimpsest miejski. Na przykładzie Katowic - Węgrzynek, Krystian (Z Teorii i Praktyki Dydaktycznej Języka Polskiego, 2020)
The article invites the readers to approach the city itself as a text of culture. We are to read it alongside other narratives/narrations (literary, artistic, and cinematic) devoted to it. The author traces how Katowice’s space has been transmuted into politically- and culturally-charged places, by distinguishing consecutive layers of the palimpsest (Polish village, building patterns of German and Polish times: the old and the new). The foregoing examples allow the author to indicate the traces of conceptions and ideologies reflected by architecture. He also includes some methodological recommendations/tips pertaining to reading the space.